Double Security of RFID Credit Cards - Khan, MAA; Qureshi, AAS; Farooqui, M (International Journal of Computer Sciences and Engineering, 2025)
Rapid advancement in RFID systems increase the need of sufficient computing power. Nowadays, more power is required to implement the encryption and decryption for the authentication during transactions. In addition, RFID tags have enough capacity to store the corresponding information. The radio waves are used in RFID technology to read the data from RFID tags. Information about the card and its owner is embedded in a tiny microchip in the e-card. The card can be read by remote machines, therefore this paper proposed double security check by introducing mobile user for the secure transaction. In addition, to provide more security to the credit card holder when his information is processed through RFID. Proposed RFID system is based on Secure Hash Algorithm and mobile communication devices such as cellular phones. It provides a secure certificate mechanism which uses a mobile phone, RFID reader and credit card containing RFID tag. Secure Hash Algorithm is used to obtain a secure and reliable way of transmitting data. The result shows that the proposed method improves the existing RFID security issues under the premise of safety, efficiency, and compatibility with the network.